2018
DOI: 10.1007/s12031-018-1042-1
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D1 Signaling: Essential Roles in Neural Stem Cell Differentiation

Abstract: Phospholipase D1 (PLD1) is generally accepted as playing an important role in the regulation of multiple cell functions, such as cell growth, survival, differentiation, membrane trafficking, and cytoskeletal organization. Recent findings suggest that PLD1 also plays an important role in the regulation of neuronal differentiation of neuronal cells. Moreover, PLD1-mediated signaling molecules dynamically regulate the neuronal differentiation of neural stem cells (NSCs). Rho family GTPases and Ca2+-dependent sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…6 (27,28,31,32). PLD1 produces PA, which activates SHP-1 (26,97), a phosphatase that inhibits BCR-associated kinases and downregulates BCR signaling (71, 72, 75, 98, 99) (Fig. 6A).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 (27,28,31,32). PLD1 produces PA, which activates SHP-1 (26,97), a phosphatase that inhibits BCR-associated kinases and downregulates BCR signaling (71, 72, 75, 98, 99) (Fig. 6A).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, BCALM is localized to the cytoplasm and interacts with phospholipase D 1 (PLD1) and A-kinase proteins AKAP9 (AKAP450) and AKAP13 (AKAP-Lbc). AKAPs assemble kinase signaling complexes to ensure correct subcellular targeting, including protein kinase A (PKA) and protein kinase C (PKC), which phosphorylate and activate PLD1 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). PLD1 hydrolyzes lipid membrane component phosphatidylcholine to phosphatidic acid (PA), which activates the SHP-1 phosphatase (26,31,32), a negative regulator of BCR signaling (33,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, in addition to the fact that some DEGs were VTGs or PTGs of miR-31-5p, there were interaction networks between DEGs and some VTGs of miR-31. Among them, Stat3 was an important transcription factor regulating the expression of Gfap 44 ; Sod2 played an important role in the regulation of cell cycle 45 ; and Gsk3b could be used as a signal "node" to coordinate multiple key signaling pathways in NSCs 46,47 . Based on the above analysis, we conclude that the action mechanism of miR-31 in early stage of NSCs after overexpression was not showed that in addition to the general function prediction only of COG classification, no matter the up or down regulated DEmiRNAs, distribution of PTGs were mostly in transcription, replication, recombination and repair, signal transduction mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, in addition to the fact that some DEGs were VTGs or PTGs of miR-31-5p, there were interaction networks between DEGs and some VTGs of miR-31. Among them, Stat3 was an important transcription factor regulating the expression of Gfap 44 ; Sod2 played an important role in the regulation of cell cycle 45 ; and Gsk3b could be used as a signal "node" to coordinate multiple key signaling pathways in NSCs 46 , 47 . Based on the above analysis, we conclude that the action mechanism of miR-31 in early stage of NSCs after overexpression was not only to inhibit its target gene, but also to expand its action scope by regulating the expression of other miRNAs, ultimately increasing the expression of genes or miRNAs related to NSCs stemness maintenance, and inhibiting NSCs, especially MNs, differentiation-related genes, through protein interaction and DEmiRNAs, to maintain the undifferentiated state of NSCs.…”
Section: Discussionmentioning
confidence: 99%